Adoption of integrated water resources management principles and its impacts: lessons from Ferghana Valley - Abdullaev, Iskandar; Kazbekov, Jusipbek S.; Jumaboev, Kahramon; Manthrithilake, Herath (Informa UK Limited, 2009)
The Ferghana Valley Project, initiated in 2001, has promoted institutional change in the post-Soviet irrigation sector in this part of Kyrgyzstan, Tajikistan and Uzbekistan. This paper presents the short-term (5-year) impacts of integrated water resources management project activities focused on water user participation in the South Ferghana Canal of Ferghana Province in Uzbekistan on irrigation water delivery and crop productivity. Irrigation performance assessment indicators indicate only slight improvements in water delivery and crop yields. Although water was important, larger changes in the agricultural sector of Uzbekistan dominated outcomes in this relatively short time span.